Enhancing Futsal Passing Skills Through Audio-Visual Feedback: A Study on Motor Skill Acquisition in Junior High School - Hamidi, Lianta Rohim; Manullang, Jujur Gunawan; Tambunan, Grace Kharisma (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2026)
The problem in physical education learning, particularly in futsal passing skills, is characterized by students' limited mastery of proper passing techniques, which may be associated with the limited use of instructional media that effectively demonstrate correct movement patterns. This study aimed to examine changes in students' passing skills following the implementation of audiovisual media during futsal extracurricular activities. The study employed a pre-experimental method using a one-group pretest–posttest design involving 20 students selected through total sampling. Passing skills were measured using a validated futsal passing test before and after the intervention. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-samples t-test at a significance level of 0.05. The results showed that students' passing performance improved following the audiovisual learning intervention, as reflected in an increase in the mean score from 61.70 ± 2.87 to 72.75 ± 3.06. The paired-samples t-test revealed a statistically significant difference between pretest and posttest scores (t (19) = −81.707, p < 0.001), with a mean difference of −11.05 (95% CI: −11.333 to −10.767). The novelty of this study lies in evaluating learning outcomes not only through statistical significance but also by reporting the magnitude of the observed improvement. The findings suggest that audiovisual media may support improvements in students' futsal passing skills following the learning intervention. However, causal interpretations should be drawn with caution because the study employed a one-group pretest–posttest design without a control group.